Evaluasi dan Optimalisasi Penggunaan Alokasi Dana Desa (ADD) Study Kasus Desa Maju Jaya, Sumber Mulya dan Tirta Mulya Kecamatan Pelepat Ilir Kabupaten Bungo - Yunie Rahayu; Etik Winarni (J-MAS (Jurnal Manajemen dan Sains), 2019)
Management of village fund allocation in empowering village communities is normatively and administratively good. But in substance there are several things that must be corrected, namely community participation in the planning, supervision and accountability stages, and the transparency that is not maximized because the community does not know much about the existence of these activities. The role of stakeholders in the management of village fund allocation is still not optimal, because only the village head. The results of the empowerment of village communities are still only in the form of construction of road infrastructure and irrigation channels for the construction of hamlet halls, all of which are still not or inconsistent in improving the economy of the community. Lack of in-depth socialization to the community regarding village fund allocation so that not all people know about the ADD (Village Fund Allocation) program, which in turn causes low community supervision in ADD activities and sub-district government domination of the preparation of ADD Accounts causing a lack of village independence.